PIRACY IN SOUTH EAST ASIA: INDONESIAN & REGIONAL RESPONSES - Djalal, Hasjim (UI Scholars Hub, 2021)
Piracy in high seas has caused a problem itself because there are no particular jurisdictionof any state that governed it. This particular issue falls onto universal jurisdiction in which any state has a jurisdiction to enforce their national regulation about piracy itself. On the other hand, we don’t have sufficient international instrument which obliges the contracting states initiating a cooperation between them to combat piracy. An international cooperation, and even on regional basis (such as ASEAN and Asia-Pacific region) has already taken initiatives to combat piracy. Indonesia, as one of the states involved in international and regional basis regarding combating the piracy has its own problems concerning human resources, financial resources, and facility which caused aggravation the problem of law enforcement at sea of Indonesia. Furthermore, it would cause western waters in Indonesia as basis of activity on piracy, such as Melaca Strait, Singapore Strait, Karimata Strait and South China Sea.